Collaborative Governance Process for Tourism Village Development in Semen Gandusari Village, Blitar Regency - Styareni, Ayu Apriliana Puspita; Suryawati, Dina; Prasetyo, Franciscus Adi (International Journal of Social Discussion, 2024)
The research entitled "Collaborative Governance Process in Tourism Village Development in Semen Gandusari Village, Blitar Regency" aims to describr and analyze a collaborative prcess that occurs. The type of research used in this research is descriptive qualitative research, namely to provide an averview of collaborative governance in the process of developing a tourist village in Semen Village. Data collected through indeoth interviews, observation and documentation studies. Informants are people who are trusted and know and understand the topic beig researched. Next, the data obtained was analyzed using data condensation, data presentation anf drawing conclusions and verification. The research result use the theory from Kirk Emerson and Tina Nabatchi (2015) which consists of indicators of collaboration dynamics theory, collaboration actions, impact and adaption of the collaboration process, which is very good and has a positive impact on each party involved. Institutionally, the role played by the parties involved is very active in developing the tourist village in Semen Village and the communication relationship between the village government and the parties involved is also very good, as well as the trust built in the collaboration for the development of the tourist village in Semen Village is good. Then, their sense of trust is built, so the commitment between the village government and the parties involved is very strong, especially when collaborating is guided by the District Regulation Decree, Village Decree, and AD/ART as well as cooperation agreements .